Carbon-ceramic composite material and preparation method thereof
By forming a cladding layer on the silicon/aluminum composite material of the carbon ceramic brake disc, the problems of severe reaction, high cost and uneven silicon in the existing carbon ceramic brake disc melting process are solved, and the effect of reducing the silicon seepage temperature and cost is achieved to ensure uniform dispersion of silicon.
Patent Information
- Application Number
- CN202411865475.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The existing melt-silicon seepage process of carbon ceramic brake discs has problems such as severe reactions, high production costs and uneven silicon.
The silicon/aluminum composite material is used as the silicon source for the silicon permeation process. By forming a cladding layer containing thermosetting resin, graphite, aluminum and silicon carbide on the surface of the silicon matrix, the heating temperature and cost are reduced, and the uniform dispersion of silicon is ensured.
It effectively reduces the temperature and cost of silicon seepage, ensures uniform dispersion of silicon, avoids hole blockage in trace amounts of silicon melt, and improves the compactness and mechanical properties of the carbon ceramic brake disc.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic materials, and in particular to a carbon-ceramic composite material and a preparation method thereof. Background Art
[0002] Carbon ceramic brake discs are made of carbon fiber reinforced silicon carbide-based composite materials. Due to their low density, high strength, high temperature resistance, impact resistance, good thermal conductivity, oxidation resistance and stable friction coefficient, they are widely used in aerospace and high-speed rail braking systems.
[0003] Carbon ceramic brake discs produced at home and abroad are mainly divided into two types: long fiber discs and short fiber discs. The melt siliconization process (RMI) of long fiber discs includes: melting silicon particles, infiltrating into a matrix containing long carbon fibers through capillary force, and reacting with the carbon in the matrix to form silicon carbide. The preparation steps of short fiber discs include: compression molding short carbon fibers, carbonizing to obtain a carbon-carbon embryo containing short carbon fibers, and siliconizing to obtain a short fiber disc by combining the melt siliconization process. At present, the melt siliconization process used for long fiber discs and short fiber discs is mainly carried out at 1600℃~1700℃, which has the disadvantages of violent reaction, high production cost and uneven silicon infiltration into the embryo. Summary of the invention
[0004] Based on this, the present application provides a carbon-ceramic composite material and a preparation method thereof. In the preparation method provided in the present application, by placing the silicon / aluminum composite material on the upper and lower surfaces of the coating disc embryo, it can be used as a silicon source in the melt siliconization process to reduce the heating temperature and cost in the melt siliconization process, and can ensure that the silicon infiltrated into the resin-based embryo is evenly dispersed.
[0005] In a first aspect of the present application, a method for preparing a carbon-ceramic composite material is provided, comprising the following steps:
[0006] Taking an embryo, coating the surface of the embryo with coating powder, and pressing and molding the embryo to prepare a coating preform;
[0007] Curing the coating preform at a temperature of 160° C. to 200° C. to prepare a coating disc embryo;
[0008] The preparation step of the coating powder comprises: mixing a curing resin, silicon carbide, graphite and a metal oxide in a mass ratio of (20-50):60:(5-15):(1-2), kneading at 60°C-80°C, and crushing to prepare the coating powder; the metal oxide comprises one or more of aluminum oxide and yttrium oxide;
[0009] Placing the silicon / aluminum composite material on the upper and lower surfaces of the coating disc embryo, performing a carbonization treatment at 25° C. to 900° C., and then performing a siliconizing treatment at 1400° C. to 1500° C. to prepare the carbon-ceramic composite material;
[0010] The silicon / aluminum composite material comprises a substrate and a coating layer coated on the surface of the substrate, wherein the substrate comprises silicon; the coating layer comprises a thermosetting resin, graphite, aluminum and silicon carbide;
[0011] The mass ratio of the substrate to the coating layer is (8-10): (0.3-1).
[0012] In one of the embodiments, the mass ratio of the thermosetting resin, the graphite, the aluminum element and the silicon carbide is (10-25): (5-10): (3-8): (1-2).
[0013] In one embodiment, the silicon / aluminum composite material has one or more of the following characteristics:
[0014] (1) The thermosetting resin includes a phenolic resin;
[0015] (2) The particle size of the graphite is 100 mesh to 1000 mesh;
[0016] (3) The particle size of the matrix is 1 mm to 4 mm;
[0017] (4) The particle size of the silicon carbide is 1 μm to 2 μm.
[0018] In one embodiment, the embryo body comprises a resin-based embryo body or a carbon-carbon embryo body; and the embryo body has one or more of the following characteristics:
[0019] (1) The steps of preparing the resin-based embryo include: mixing carbon fiber, solid resin and graphite powder in a mass ratio of (30-60): (25-35): (10-30) to prepare a raw material; and pressing the raw material into a shape to prepare the resin-based embryo;
[0020] (2) The steps of preparing the carbon-carbon embryo include: subjecting a carbon fiber preform to vacuum heat treatment and then subjecting it to chemical vapor deposition to prepare the carbon-carbon embryo.
[0021] In one of the embodiments, in the step of preparing the coated preform, the process parameters of the pressing molding include: a pressing temperature of 150° C. to 200° C. and a pressure of 2 MPa to 4 MPa.
[0022] In one embodiment, the preparation method has one or more of the following characteristics:
[0023] (1) In the step of preparing the resin-based embryo, the process parameters of the pressing molding include: a pressing temperature of 150° C. to 200° C. and a pressure of 2 MPa to 4 MPa;
[0024] (2) In the step of preparing the carbon-carbon embryo, the process parameters of the vacuum heat treatment include: pressure <1 kPa, temperature 900°C~1100°C;
[0025] (3) In the step of preparing the carbon-carbon embryo, the process parameters of chemical vapor deposition include: the chemical reaction gas is natural gas and propane, the deposition pressure is 1.5 kPa~2.5 kPa, and the deposition temperature is 950℃~1000℃.
[0026] In one embodiment, the steps of preparing the silicon / aluminum composite material include:
[0027] The thermosetting resin, graphite powder, aluminum powder, silicon carbide and an organic solvent are mixed to prepare a slurry;
[0028] The substrate is mixed with the slurry, and after drying, the silicon / aluminum composite material is prepared;
[0029] Wherein, the mass ratio of the matrix and the slurry is (8-10):1.
[0030] In one embodiment, the mass ratio of the thermosetting resin, the graphite powder, the aluminum powder, the silicon carbide and the organic solvent is (10-25): (5-10): (3-8): (1-2): (8-15).
[0031] In one embodiment, the drying process parameters include: a temperature of 75°C to 85°C.
[0032] A second aspect of the present application provides a carbon-ceramic composite material, which is prepared by the preparation method of the carbon-ceramic composite material described in any embodiment of the first aspect of the present application.
[0033] In the preparation method of the carbon-ceramic composite material provided in the present application, a coating disc embryo is prepared by specific steps, and a specific silicon / aluminum composite material is selected as silicon particles for siliconization treatment. The two cooperate with each other to effectively reduce the siliconization temperature and the risk of uneven siliconization. Specifically, the silicon / aluminum composite material is a coating layer containing thermosetting resin, aluminum, graphite and silicon carbide formed on the surface of the silicon substrate, and the mass ratio of the substrate and the coating layer is further defined. On the one hand, the aluminum element in the coating layer can effectively reduce the heating temperature and cost during the molten siliconization process; at the same time, the cross-linking of the resin in the coating layer can protect the silicon substrate, avoid the oxidation reaction of the silicon substrate and cause the melting point of the material to rise, and the addition of silicon carbide can facilitate the cleaning of the siliconization tooling after the siliconization treatment.
[0034] Furthermore, the silicon / aluminum composite material provided in the present application is used as a silicon source for the molten siliconization process in the preparation of a carbon-ceramic composite material or a carbon-ceramic brake disc. In the siliconization treatment step, the carbon generated by the carbonization of the thermosetting resin and the graphite powder will react with the silicon matrix to form a coating layer containing silicon carbide; subsequently, continuous heating is performed to melt the silicon matrix, but due to the coating effect of the coating layer, a trace amount of molten silicon cannot overflow; as the heating time increases, the molten silicon overflows the coating layer, causing a large amount of molten silicon to infiltrate the resin-based embryo, thereby avoiding the pore blocking phenomenon caused by incomplete infiltration of a trace amount of molten silicon, and making the silicon in the carbon-ceramic brake disc evenly dispersed. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 A physical picture of the carbon ceramic brake disc prepared in Example 1 of the present application;
[0036] Figure 2 A physical picture of the carbon ceramic brake disc prepared in Example 2 of the present application;
[0037] Figure 3 This is a microstructure diagram of siliconization in the resin-based embryonic body of the carbon-ceramic brake disc prepared in Example 1 of the present application;
[0038] Figure 4 This is a microstructure diagram of siliconization in the resin-based embryonic body of the carbon-ceramic brake disc prepared in Comparative Example 1 of the present application;
[0039] Figure 5 This is a microstructure diagram of the coating in the carbon-ceramic brake disc prepared in Example 2 of the present application. DETAILED DESCRIPTION
[0040] The carbon-ceramic composite material and its preparation method of the present application are further described in detail and in detail below in conjunction with specific examples. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.
[0041] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0042] As used herein, "one or more" refers to any one, any two, or any two or more of the listed items.
[0043] In this application, "first aspect", "second aspect", "third aspect", "fourth aspect", "fifth aspect", etc. are used only for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first", "second", "third", "fourth", "fifth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.
[0044] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0045] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0046] The percentage contents involved in this application, unless otherwise specified, refer to mass percentage for solid-liquid mixing and solid-solid mixing, and refer to volume percentage for liquid-liquid mixing.
[0047] The percentage concentrations mentioned in this application, unless otherwise specified, refer to the final concentration, which refers to the percentage of the added component in the system after the addition of the component.
[0048] The temperature parameters in this application, unless otherwise specified, allow for both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the accuracy range of instrument control.
[0049] In a first aspect of the present application, a method for preparing a carbon-ceramic composite material is provided, comprising the following steps:
[0050] S40. Take the embryo, apply coating powder on the surface of the embryo, and press it into shape to prepare a coating preform.
[0051] S50. Curing the coated preform at a temperature of 160° C. to 200° C. to prepare the coated disc embryo.
[0052] S60. Placing the silicon / aluminum composite material on the upper and lower surfaces of the coating disc embryo, performing a carbonization treatment at 25° C. to 900° C., and then performing a siliconizing treatment at 1400° C. to 1500° C. to prepare the carbon-ceramic composite material.
[0053] The silicon / aluminum composite material comprises a substrate and a coating layer coated on the surface of the substrate, wherein the substrate comprises silicon; the coating layer comprises a thermosetting resin, graphite, aluminum and silicon carbide;
[0054] The mass ratio of the substrate to the coating layer is (8-10): (0.3-1).
[0055] The preparation method of the carbon-ceramic composite material provided in the present application selects a silicon / aluminum composite material as silicon particles for siliconization treatment, wherein the silicon / aluminum composite material forms a coating layer containing thermosetting resin, aluminum, graphite and silicon carbide on the surface of a silicon substrate, and further limits the mass ratio of the substrate and the coating layer. On the one hand, the aluminum element in the coating layer can effectively reduce the heating temperature and cost during the molten siliconization process; at the same time, the cross-linking of the resin in the coating layer can protect the silicon substrate, avoiding the oxidation reaction of the silicon substrate and causing the melting point of the material to rise, and the addition of silicon carbide can facilitate the cleaning of the siliconization tooling after the siliconization treatment.
[0056] Furthermore, the silicon / aluminum composite material provided in the present application can be used as a silicon source for the molten siliconization process in the preparation of carbon-ceramic brake discs. In the carbonization step, the carbon generated by the carbonization of the thermosetting resin and the graphite powder will react with the silicon matrix to form a coating layer containing silicon carbide; the subsequent siliconization treatment melts the silicon matrix, but due to the coating effect of the coating layer, a trace amount of molten silicon cannot overflow; as the heating time increases, the molten silicon overflows the coating layer, allowing a large amount of molten silicon to infiltrate the resin-based embryo, thereby avoiding the pore blocking phenomenon caused by incomplete infiltration of a trace amount of molten silicon, and making the silicon in the carbon-ceramic brake disc evenly dispersed.
[0057] It can be understood that in the present application, the mass ratio of the silicon substrate and the coating layer can be selected from any value between (8~10): (0.3~1). Specifically, the mass ratio of the silicon substrate and the coating layer includes but is not limited to 8:0.3, 8:0.5, 8:1, 9:0.3, 9:0.5, 9:1, 10:0.3, 10:0.5 or 10:1. Limiting the mass ratio of the silicon substrate and the coating layer to this range can ensure that the coating layer covers the substrate and modifies the substrate; it can also reduce the impact of too many impurities in the coating layer entering the coated disc embryo during the subsequent melt siliconization process on the mechanical properties of the carbon-ceramic composite material.
[0058] In one example, the mass ratio of the thermosetting resin, the graphite, the aluminum element and the silicon carbide is (10-25): (5-10): (3-8): (1-2). It can be understood that in the present application, the mass ratio of the thermosetting resin, the graphite, the aluminum element and the silicon carbide can be selected from any value between (10-25): (5-10): (3-8): (1-2). Specifically, the mass ratio of the thermosetting resin, the graphite and the aluminum element includes but is not limited to 10:5:3:1, 12:8:4:1, 15:8:5:1, 18:8:5:1, 20:8:5:2, 22:9:7:2 or 25:10:8:2. The mass ratio of thermosetting resin, graphite, aluminum and silicon carbide is selected within the above range. The thermosetting resin, as the main component of the coating layer, can effectively coat the silicon substrate, and further reduce the melting point of the silicon / aluminum composite material in cooperation with a specific mass ratio of graphite, aluminum and silicon carbide.
[0059] In one example, the thermosetting resin includes a phenolic resin.
[0060] In one example, the particle size of the graphite is 100 mesh to 1000 mesh.
[0061] In one example, the particle size of the matrix is 1 mm to 4 mm.
[0062] In one example, the grain size of the silicon carbide is 1 μm to 2 μm.
[0063] The preparation method of the carbon-ceramic composite material provided in the present application includes the preparation of the embryo, the preparation of the coating powder, and the preparation of the coating disc embryo, which are specifically as follows:
[0064] The embryo body includes a resin-based embryo body or a carbon-carbon embryo body.
[0065] For example, the steps of preparing the resin-based embryo body include:
[0066] S10. The carbon fiber, the solid resin and the graphite powder are mixed in a mass ratio of (30-60): (25-35): (10-30) to prepare a raw material;
[0067] S20. After the raw material is pressed into shape, the resin-based embryo body is prepared.
[0068] Preferably, in step S10, the mixing process parameters include: the mixing temperature is 25°C~60°C, and the mixing speed is 50r / min~300r / min. In step S20, the process parameters of press molding include: the pressing temperature is 150°C~200°C, and the pressure is 2MPa~4MPa. Specifically, the steps of step S20 are: putting the raw materials into the mold, covering the mold cover plate, placing it in a flat vulcanizer for press molding, the pressing pressure is 2MPa~4MPa, the pressing temperature is 150°C~200°C, and the pressing time is 20min~40min; after molding, after cooling and demolding, the resin-based embryo is prepared.
[0069] Specifically, in step S10, the carbon fiber includes one or more of short carbon fiber and long carbon fiber. For example, the long carbon fiber includes but is not limited to 24k T700 carbon fiber or 12k T700 carbon fiber. The preparation step of the short carbon fiber includes: pre-compressing and bundling the 24k (or 12k) T700 carbon fiber to prepare a bundle; using sizing fiber to size the surface of the bundle, and then chopping it into short fibers with a length of 8mm~15mm; wherein the mass percentage of polyurethane or epoxy resin contained in the sizing fiber is 3%~5%.
[0070] In one example, in step S10, the selected solid resin includes solid phenolic resin.
[0071] For example, the step of preparing the carbon-carbon embryo includes: subjecting a carbon fiber preform to vacuum heat treatment, and then subjecting it to chemical vapor deposition to prepare the carbon-carbon embryo.
[0072] In one example, in the step of preparing the carbon-carbon embryo, the process parameters of the vacuum heat treatment include: pressure <1 kPa, temperature 900°C~1100°C.
[0073] In one example, in the step of preparing the carbon-carbon embryo, the process parameters of chemical vapor deposition include: the chemical reaction gas is natural gas and propane, the deposition pressure is 1.5 kPa~2.5 kPa, and the deposition temperature is 950℃~1000℃.
[0074] The preparation steps of the coating powder include:
[0075] S30. The curing resin, silicon carbide, graphite and metal oxide are mixed in a mass ratio of (20-50):60:(5-15):(1-2), and the mixture is kneaded at 60°C-80°C and crushed to prepare the coating powder. It is understood that in step S30, a small amount of a second organic solvent may be added to enhance the formability of the coating powder. The second organic solvent may be, for example, alcohol.
[0076] In one example, in step S30, the metal oxide includes one or more of aluminum oxide and yttrium oxide. Preferably, the metal oxide includes aluminum oxide and yttrium oxide in a mass ratio of 5: (1.5-2.5). It is understood that the mass ratio of aluminum oxide to yttrium oxide includes but is not limited to 5:1.6, 5:1.8, 5:2, 5:2.1, 5:2.2 or 5:2.4.
[0077] In one example, in step S30, the curing resin includes one or more of a solid phenolic resin and a solid furan resin. In one example, the banburying temperature of step S30 can be selected from any value between 60°C and 80°C. Specifically, the banburying temperature includes but is not limited to 62°C, 65°C, 70°C, 75°C or 80°C.
[0078] In one example, in the coated preform, the thickness of the coating is 3 mm to 5 mm.
[0079] In step S50, the curing temperature includes but is not limited to 162°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 198°C or 200°C.
[0080] In one example, after the step of preparing the coated disc embryo in step S50, the step of machining the coated disc embryo is also included, wherein the machining method includes but is not limited to turning, cutting, milling or grinding.
[0081] In one example, step S60 further includes a step of coating boron nitride powder on the surface of the siliconizing tooling before placing the silicon / aluminum composite material on the upper and lower surfaces of the coated disc blank prepared in step S50.
[0082] Specifically, step S60 includes the following processes: a. Take a siliconizing tool and apply boron nitride powder on the surface and sidewall of the siliconizing tool; b. Then place a layer of graphite paper on the surface of the siliconizing tool, and then spread the silicon / aluminum composite material on the surface of the graphite paper, and place the coated disc blank; c. Then place the silicon / aluminum composite material on the surface of the coated disc blank, and perform carbonization and siliconizing treatment. Preferably, the mass ratio of the silicon / aluminum composite material added to the upper surface and the lower surface of the coated disc blank is 1: (2-4).
[0083] Siliconizing treatment is carried out at 1400℃~1500℃. Due to the presence of aluminum in the surface of the silicon / aluminum composite material, the silicon matrix has been basically melted. At the same time, the green body is carbonized to form a porous carbon green body. Due to the action of capillary force, molten silicon can penetrate into the porous carbon green body. In addition, the solid resin contained in the resin-based green body is relatively loose and easier to react with liquid silicon to react to form a dense silicon carbide matrix, which fills the pores of the carbon fiber, and finally obtains a dense carbon-ceramic composite material.
[0084] In one specific example, in step S60, the specific steps of carbonization treatment include: (1) heating from room temperature to 180°C~220°C within 50min~70min for a first carbonization process; keeping at 180°C~220°C for 20min~40min for a second carbonization process; heating from 180°C~220°C to 340°C~360°C within 50min~70min for a third carbonization process; keeping at 340°C~360°C for 20min~40min for a fourth carbonization process; heating from 340°C~360°C to 590°C~610°C within 80min~100min for a fifth carbonization process; keeping at 590°C~610°C for 20min~40min for a sixth carbonization process; heating from 590°C~610°C to 850°C~900°C within 110min~130min for a seventh carbonization process.
[0085] In one of the examples, in step S60, the specific steps of performing siliconizing treatment include: the siliconizing process is: heating from 850℃~900℃ to 1400℃~1450℃ within 190min~220min to perform the first siliconizing process; keeping warm at 1400℃~1450℃ for 50min~70min to perform the second siliconizing process; heating from 1400℃~1450℃ to 1480℃~1500℃ within 140min~160min to perform the third siliconizing process; keeping warm at 1480℃~1500℃ for 300min to perform the fourth siliconizing treatment.
[0086] In one example, the step of post-processing the carbon-ceramic composite material prepared in step S60 is also included:
[0087] S70. Immerse the carbon-ceramic composite material prepared in step S60 in an anti-oxidation solution, take it out, and sinter it at 200° C. to 300° C. to prepare a carbon-ceramic composite material containing an anti-oxidation coating.
[0088] S80. Fine-processing the carbon-ceramic composite material containing the anti-oxidation coating prepared in step S70 to prepare a finished carbon-ceramic composite material.
[0089] In one example, in step S70, the anti-oxidation solution includes one or more of aluminum dihydrogen phosphate, aluminum chromium phosphate, boric acid, zirconium oxide, nickel oxide and strontium oxide. Preferably, in step S70, the anti-oxidation solution includes aluminum dihydrogen phosphate, zirconium oxide, boric acid and aluminum oxide in a mass ratio of (85~95):(1~3):(1~10):(1~3). It can be understood that oxides such as zirconium oxide, nickel oxide and strontium oxide have low solubility. After adding the aforementioned oxides, the anti-oxidation solution is in a suspension state. Specifically, the mass ratio of aluminum dihydrogen phosphate, zirconium oxide, boric acid and aluminum oxide in the anti-oxidation solution includes but is not limited to 85:3:9:3, 86:2:9, 90:1:8:1, 92:1:5:2 or 95:1:3:1.
[0090] In one example, the method for preparing the silicon / aluminum composite material comprises the following steps:
[0091] S1. The thermosetting resin, graphite powder, aluminum powder, silicon carbide and an organic solvent are mixed to prepare a slurry;
[0092] S2. The substrate is mixed with the slurry, and after drying, the silicon / aluminum composite material is prepared.
[0093] Wherein, in step S1, the mass ratio of the matrix and the slurry is (8-10): 1. By limiting the mass ratio of the matrix and the slurry, it is helpful to control the mass ratio of the subsequent matrix and the coating layer. It can be understood that since the slurry is to be prepared in step S1, the thermosetting resin in step S1 is preferably a liquid phenolic resin, and the selected liquid phenolic resin becomes solid after being dried in step S2.
[0094] In one example, in step S1, the mass ratio of the thermosetting resin, the graphite powder, the aluminum powder, the silicon carbide and the organic solvent is (10-25): (5-10): (3-8): (1-2): (8-15).
[0095] In one example, in step S2, the drying process parameters include: a temperature of 75°C to 85°C. At this drying temperature, the liquid resin can be cross-linked and cured into a thermosetting resin to prepare a coating layer including a thermosetting resin, graphite and aluminum. It can be understood that the present application does not limit the form of graphite and aluminum in step S1, and graphite powder and aluminum powder well known to those skilled in the art can be used. In one example, in order to reduce the grinding step, graphite powder and aluminum powder are preferably used. Among them, the particle size of the graphite powder is 100 mesh to 1000 mesh.
[0096] In a second aspect of the present application, a carbon-ceramic composite material is provided, which is prepared by the method for preparing the carbon-ceramic composite material described in the present application. Specifically, the steps for preparing the carbon-ceramic composite material include:
[0097] S100. preparing a raw material by mixing carbon fiber, solid resin and graphite powder in a mass ratio of (30-60): (25-35): (10-30) at a temperature of 25°C-60°C and a rotation speed of 50r / min-300r / min;
[0098] S200. The raw material is pressed and molded at a temperature of 150° C. to 200° C. and a pressure of 2 MPa to 4 MPa, and after cooling and demolding, the resin-based embryo body is prepared.
[0099] S300. The curing resin, silicon carbide, graphite and metal oxide are mixed in a mass ratio of (20-50):60:(5-15):(1-2), kneaded at 60°C-80°C, and crushed to prepare the coating powder; wherein the metal oxide includes aluminum oxide and yttrium oxide in a mass ratio of 5:(1.5-2.5).
[0100] S400. Taking the resin-based embryo prepared in step S200, applying the coating powder prepared in step S300 on the surface of the resin-based embryo, and pressing to prepare a coating preform;
[0101] S500. Curing the coated preform at a temperature of 160° C. to 200° C. and machining the preform to prepare the coated disc embryo.
[0102] S600. Place the coated disc blank in step S500 in a siliconizing tool, apply boron nitride powder on the surface of the tool, add silicon / aluminum composite materials to the upper and lower surfaces of the carbon fiber blank, respectively, perform carbonization treatment at 25°C to 900°C, and then perform siliconizing treatment at 900°C to 1450°C to prepare a carbon-ceramic composite material.
[0103] S700. Immerse the carbon-ceramic composite material prepared in step S600 in an anti-oxidation solution, take it out, and sinter it at 200° C. to 300° C. to prepare a carbon-ceramic composite material containing an anti-oxidation coating.
[0104] S800. Fine-processing the carbon-ceramic composite material containing the anti-oxidation coating prepared in step S700 to prepare a carbon-ceramic brake disc.
[0105] Alternatively, the steps of preparing the carbon-ceramic composite material include:
[0106] S100. Preparing carbon fiber into a carbon fiber preform.
[0107] S200. The carbon fiber preform is subjected to vacuum heat treatment and then subjected to chemical vapor deposition to prepare the carbon-carbon embryo; wherein the process parameters of the vacuum heat treatment include: pressure <1 kPa, temperature of 900°C~1100°C; the process parameters of the chemical vapor deposition include: the chemical reaction gas is natural gas and propane, the deposition pressure is 1.5 kPa~2.5 kPa, and the deposition temperature is 950°C~1000°C.
[0108] S300. The curing resin, silicon carbide, graphite and metal oxide are mixed in a mass ratio of (20-50):60:(5-15):(1-2), kneaded at 60°C-80°C, and crushed to prepare the coating powder; wherein the metal oxide includes aluminum oxide and yttrium oxide in a mass ratio of 5:(1.5-2.5).
[0109] S400. Taking the carbon-carbon embryo prepared in step S200, applying the coating powder prepared in step S300 on the surface of the carbon-carbon embryo, and pressing to prepare a coating preform;
[0110] S500. Curing the coated preform at a temperature of 160° C. to 200° C. and machining the preform to prepare the coated disc embryo.
[0111] S600. Place the coated disc blank in step S500 in a siliconizing tool, apply boron nitride powder on the surface of the tool, add silicon / aluminum composite materials to the upper and lower surfaces of the carbon fiber blank, respectively, perform carbonization treatment at 25°C to 900°C, and then perform siliconizing treatment at 900°C to 1450°C to prepare a carbon-ceramic composite material.
[0112] S700. Immerse the carbon-ceramic composite material prepared in step S600 in an anti-oxidation solution, take it out, and sinter it at 200° C. to 300° C. to prepare a carbon-ceramic composite material containing an anti-oxidation coating.
[0113] S800. Fine-processing the carbon-ceramic composite material containing the anti-oxidation coating prepared in step S700 to prepare a carbon-ceramic brake disc.
[0114] The silicon / aluminum composite material prepared in the present application has a silicon substrate surface coated with a coating layer containing thermosetting resin, graphite, aluminum and silicon carbide. Due to the presence of aluminum, it can effectively reduce the melting point of the silicon / aluminum composite material, and then in step S600, the temperature of carbonization and siliconization treatment can be effectively reduced to reduce costs; at the same time, the resin on the silicon substrate surface will react with the silicon substrate surface during high-temperature carbonization to form a thin silicon carbide shell, which is beneficial to the centralized release of silicon liquid during siliconization and improves the uniformity of siliconization; and the presence of silicon carbide can effectively increase the cleaning rate of siliconizing tooling. Furthermore, in step S600, during the continuous carbonization and siliconization process, the thermosetting resin and graphite powder in the silicon / aluminum composite material coating layer can be carbonized and form a coating layer containing silicon carbide with the silicon matrix. The existence of the coating layer can avoid the dissolution of trace silicon melt, thereby effectively avoiding the uneven siliconization of the coating disc blank caused by the trace silicon melt; as the heating time increases, a large amount of silicon melt overflows the coating layer, thereby achieving uniform siliconization of the coating disc blank to prepare a carbon-ceramic composite material with uniform silicon distribution.
[0115] The following are specific examples. Unless otherwise specified, the raw materials used in the examples are all commercially available. The following specific examples are intended to further explain the present invention in detail to help the technical personnel and researchers in the field to further understand the present invention. The relevant technical conditions do not constitute any limitation to the present invention. Any form of modification made within the scope of the claims of the present invention is within the scope of protection of the claims of the present invention.
[0116] Preparation Example 1
[0117] Preparation Example 1 of the present application provides a silicon / aluminum composite material and a preparation method thereof, comprising the following steps:
[0118] (1) preparing a slurry by mixing liquid phenolic resin, graphite powder, aluminum powder, silicon carbide and alcohol in a ratio of 20:10:8:1:15;
[0119] (2) Silicon particles with a particle size of 2 mm to 4 mm are mixed with the slurry in step (1) at a mass ratio of 10:1, and dried at 80° C. to solidify the liquid resin, thereby preparing the silicon / aluminum composite material.
[0120] Preparation Example 2
[0121] Preparation Example 2 only uses silicon particles with a particle size of 2 mm to 4 mm.
[0122] Example 1
[0123] Embodiment 1 of the present application provides a carbon ceramic brake disc and a method for preparing the same, comprising the following steps:
[0124] (1) 12k T700 carbon fiber is pre-compressed and bundled to prepare a bundle; the bundle surface is sized using sizing fibers, and then the bundle is chopped into short fibers with a length of 8 mm to 15 mm; wherein the mass percentage of polyurethane and epoxy resin contained in the sizing fibers is 3% to 5%.
[0125] (2) mixing short carbon fibers, solid phenolic resin, and graphite powder in a mass ratio of 55:30:15 at a temperature of 60° C. and a rotation speed of 100 r / min to prepare a raw material;
[0126] (3) The raw material is pressed and molded at a temperature of 200° C. and a pressure of 2 MPa for 40 min. After cooling and demolding, a resin-based embryo is prepared. The density of the resin-based embryo is 1.4 g / cm 3 .
[0127] (4) Solid phenolic resin, silicon carbide, graphite powder and oxides are mixed in a mass ratio of 30:60:8:2, wherein the oxides include aluminum oxide and yttrium oxide in a mass ratio of 5:2, and the mixture is kneaded at 80° C. and crushed to prepare the coating powder.
[0128] (5) taking the resin-based embryo body prepared in step (3), coating the coating powder prepared in step (4) on the surface of the resin-based embryo body, and pressing and molding to prepare a coating preform;
[0129] (6) Curing the coated preform at 200° C. and machining the preform to prepare a coated disc blank.
[0130] (7) Take a siliconizing tool, apply boron nitride powder on the surface of the siliconizing tool, place a layer of graphite paper on the surface of the siliconizing tool after applying the boron nitride powder, and then place the coated disc blank; add the silicon / aluminum composite material of Preparation Example 1 on the upper and lower surfaces of the coated disc blank, respectively, so that the mass ratio of the silicon / aluminum composite material located on the upper surface of the carbon fiber blank and the mass ratio of the silicon / aluminum composite material located on the lower surface of the carbon fiber blank is 1:4, and perform carbonization and siliconization treatment to prepare a carbon-ceramic composite material, wherein the specific parameters of the carbonization and siliconization treatments are shown in Table 1.
[0131] (8) The carbon-ceramic composite material prepared in step (7) is immersed in an anti-oxidation solution, taken out, and sintered at 300° C. to prepare a carbon-ceramic composite material containing an anti-oxidation coating; wherein the anti-oxidation solution comprises aluminum dihydrogen phosphate, zirconium oxide, boric acid and aluminum oxide in a mass ratio of 95:1:3:1.
[0132] (9) The carbon-ceramic composite material containing the anti-oxidation coating prepared in step (8) is finely processed to prepare a carbon-ceramic brake disc. The actual picture of the prepared carbon-ceramic brake disc is as follows: Figure 1 As shown, the microstructure of the coating in Example 1 is shown in Figure 5 As shown. The carbonization process in Table 1 is: the first carbonization process is carried out from room temperature to 200℃ within 60min; the second carbonization process is carried out at 200℃ for 30min; the third carbonization process is carried out from 200℃ to 350℃ within 60min; the fourth carbonization process is carried out at 350℃ for 30min; the fifth carbonization process is carried out from 350℃ to 600℃ within 90min; the sixth carbonization process is carried out at 600℃ for 30min; the seventh carbonization process is carried out from 600℃ to 900℃ within 120min. The siliconization process is: the first siliconization process is carried out from 900℃ to 1420℃ within 210min; the second siliconization process is carried out at 1420℃ for 60min; the third siliconization process is carried out from 1420℃ to 1480℃ within 30min; the fourth siliconization process is carried out at 1480℃ for 150min.
[0133] Table 1
[0134]
[0135] Comparative Example 1
[0136] Comparative Example 1 is basically the same as Example 1, and the main difference is that in step (7) of Comparative Example 1, the silicon particles provided in Comparative Example 2 are added to the upper surface and the lower surface of the coated disc embryo respectively. At the same time, the specific parameters of the carbonization treatment and siliconization treatment in step (7) of Comparative Example 1 are shown in Table 2. The carbonization process in Table 2 is: heating from room temperature to 200°C within 60 minutes for the first carbonization process; keeping at 200°C for 30 minutes for the second carbonization process; heating from 200°C to 350°C within 60 minutes for the third carbonization process; keeping at 350°C for 30 minutes for the fourth carbonization process; heating from 350°C to 600°C within 90 minutes for the fifth carbonization process; keeping at 600°C for 30 minutes for the sixth carbonization process; heating from 600°C to 900°C within 120 minutes for the seventh carbonization process. The siliconizing process is as follows: the temperature is raised from 900°C to 1420°C within 210 minutes for the first siliconizing process; the temperature is kept at 1420°C for 60 minutes for the second siliconizing process; the temperature is raised from 1420°C to 1700°C within 150 minutes for the third siliconizing process; and the temperature is kept at 1700°C for 300 minutes for the fourth siliconizing process.
[0137] Table 2
[0138]
[0139] Example 2
[0140] Example 2 is basically the same as Example 1, with the main difference being that Example 2 does not include step (4), step (5) and step (6). Step (7) directly places the resin-based embryo in step (3) into the siliconizing tooling. The actual picture of the carbon ceramic brake disc prepared in Example 2 is as shown in FIG. Figure 2 shown.
[0141] Comparative Example 2
[0142] Comparative Example 2 is basically the same as Example 2, and the main difference is that in step (7) of Comparative Example 2, the silicon particles provided in Preparation Example 2 are added to the upper surface and the lower surface of the coated disc blank, respectively. At the same time, the specific parameters of the carbonization treatment and siliconization treatment in step (7) of Comparative Example 2 are shown in Table 3. The carbonization process in Table 3 is: heating from room temperature to 200°C within 60 minutes for the first carbonization process; keeping at 200°C for 30 minutes for the second carbonization process; heating from 200°C to 350°C within 60 minutes for the third carbonization process; keeping at 350°C for 30 minutes for the fourth carbonization process; heating from 350°C to 600°C within 90 minutes for the fifth carbonization process; keeping at 600°C for 30 minutes for the sixth carbonization process; heating from 600°C to 900°C within 120 minutes for the seventh carbonization process. The siliconizing process is as follows: the temperature is raised from 900°C to 1420°C within 210 minutes for the first siliconizing process; the temperature is kept at 1420°C for 60 minutes for the second siliconizing process; the temperature is raised from 1420°C to 1700°C within 150 minutes for the third siliconizing process; and the temperature is kept at 1700°C for 300 minutes for the fourth siliconizing process.
[0143] Table 3
[0144]
[0145] Example 3
[0146] Example 3 is basically the same as Example 1, the main difference being that steps (1) to (5) are different. Specifically, the process of steps (1) to (5) of Example 3 is as follows:
[0147] (1) Prefabricating: Using conventional technology, a full carbon fiber needle-punched felt is made using T700-grade carbon fiber, and the prefabricated structure of the ring-shaped matrix is cut into pieces according to the specifications of the brake disc;
[0148] (2) Vacuum heat treatment: placing the preform obtained in step (1) into a CVD furnace for vacuum heat treatment at a temperature of 1000°C, a pressure of less than 1 kPa, and a holding time of 2 h;
[0149] (3) Chemical vapor deposition: placing the preform subjected to vacuum heat treatment in step (2) into a chemical vapor deposition furnace for chemical vapor deposition until the density of the preform reaches 1.35 g / cm³, wherein the chemical vapor deposition uses natural gas and propane as chemical reaction gases, the deposition pressure is 2 kPa, the deposition temperature is 980°C, and the deposition time is 200 h; obtaining a carbon-carbon embryo;
[0150] (4) Solid phenolic resin, silicon carbide, graphite powder and oxides are mixed in a mass ratio of 30:60:8:2, wherein the oxides include aluminum oxide and yttrium oxide in a mass ratio of 5:2, and the mixture is kneaded at 80° C. and crushed to prepare the coating powder.
[0151] (5) Take the carbon-carbon embryo prepared in step (3), apply the coating powder prepared in step (4) on the surface of the carbon-carbon embryo, and press it into shape to prepare a coating preform.
[0152] Comparative Example 3
[0153] Comparative Example 3 is basically the same as Example 3, and the main difference is that in step (7) of Comparative Example 3, the silicon particles provided in Preparation Example 2 are added to the upper surface and the lower surface of the coated disc embryo respectively. At the same time, the specific parameters of the carbonization treatment and siliconization treatment in step (7) of Comparative Example 3 are shown in Table 4. The carbonization process in Table 4 is: heating from room temperature to 200°C within 60 minutes for the first carbonization process; keeping at 200°C for 30 minutes for the second carbonization process; heating from 200°C to 350°C within 60 minutes for the third carbonization process; keeping at 350°C for 30 minutes for the fourth carbonization process; heating from 350°C to 600°C within 90 minutes for the fifth carbonization process; keeping at 600°C for 30 minutes for the sixth carbonization process; heating from 600°C to 900°C within 120 minutes for the seventh carbonization process. The siliconizing process is as follows: the temperature is raised from 900°C to 1420°C within 210 minutes for the first siliconizing process; the temperature is kept at 1420°C for 60 minutes for the second siliconizing process; the temperature is raised from 1420°C to 1700°C within 150 minutes for the third siliconizing process; and the temperature is kept at 1700°C for 300 minutes for the fourth siliconizing process.
[0154] Table 4
[0155]
[0156] The differences between the preparation methods of the above examples and comparative examples are shown in Table 5.
[0157] Table 5
[0158]
[0159] The carbon ceramic brake discs of the above embodiment and comparative example were tested for density and porosity. The test process is: the density and porosity of the carbon ceramic brake discs were tested using the Archimedes drainage method. The corresponding test results are shown in Table 6.
[0160] Table 6
[0161]
[0162] It can be seen from Table 6 that in the embodiments and comparative examples of the present application, the density of the carbon ceramic brake disc is between 2 g / cm 3 ~2.25g / cm 3 It has a lower volume density and a porosity distribution between 2% and 4%, which indicates that the present application selects the silicon / aluminum composite material in Preparation Example 1 and lowers the siliconizing temperature, so that the prepared carbon-ceramic brake disc can be basically dense and the siliconizing effect is better.
[0163] The carbon ceramic brake discs of the above embodiment and comparative example were subjected to mechanical property tests. The tensile strength, bending strength and impact toughness of the samples were tested using an electronic universal testing machine; the tensile strength sample size (dumbbell-shaped sample) was 120mm*18mm*4mm; the bending strength sample size was 55mm*10mm*4mm; the impact toughness sample size was 55mm*10mm*10mm. The corresponding test results are shown in Table 7.
[0164] Table 7
[0165]
[0166] The mechanical properties test data of the embodiments and comparative examples are shown in Table 7 above. It can be clearly seen that the embodiments 1 to 3 of the present application can more effectively improve the tensile strength and bending strength of the carbon ceramic brake disc on the basis of achieving the impact toughness corresponding to the comparative examples 1 to 3. Furthermore, compared with the embodiment 1, the embodiment 2 does not include the coating treatment step, resulting in slightly poor tensile strength and bending strength in the embodiment 2. Accordingly, Figure 3 This is a microstructure diagram of the carbon ceramic brake disc prepared in Example 1. Figure 4 The microstructure of the carbon ceramic brake disc prepared in Comparative Example 1 is shown in FIG. Figure 3 It can be seen that the carbon ceramic brake disc prepared in Example 1 of the present application has a large amount of silicon infiltration, and the silicon particles infiltrated into the matrix are small and evenly dispersed, thereby improving the tensile strength and bending strength of the carbon ceramic brake disc. Therefore, the use of the silicon / aluminum composite material in Preparation Example 1 can not only effectively reduce the silicon infiltration temperature, but also ensure uniform silicon infiltration, thereby improving the tensile strength and bending strength of the carbon ceramic brake disc.
[0167] The carbon ceramic brake discs of the above-mentioned embodiments and comparative examples were subjected to friction performance tests. The specific test method is as follows: the JF122 series automobile brake inertia test bench of Jilin Jida Electromechanical Equipment Co., Ltd. was used to conduct simulated braking tests on the carbon ceramic brake disc samples of the embodiments and comparative examples; the experiments were conducted based on the SAE J2522 standard; the standard includes various performance tests on the brake discs, and is based on the structure, demonstration and partial definition of the current European AK Master test method version. The corresponding test results are shown in Table 8.
[0168] Table 8
[0169]
[0170] It can be seen from Table 8 that the samples of the above embodiments all maintain good friction performance and meet the requirement that the friction coefficient of the brake disc is higher than 0.38. At the same time, between Example 2 and Comparative Example 2, and between Example 3 and Comparative Example 3, the friction coefficients obtained by Example 2 and Example 3 are greater. In addition, the brake disc in Example 2 is not coated, resulting in a slightly lower friction coefficient.
[0171] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0172] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a carbon-ceramic composite material, characterized in that: The following steps are involved: Taking an embryo, coating the surface of the embryo with coating powder, and pressing and molding the embryo to prepare a coating preform; Curing the coating preform at a temperature of 160° C. to 200° C. to prepare a coating disc embryo; Placing a silicon / aluminum composite material on the upper and lower surfaces of the coating disc embryo, performing a carbonization treatment at 25° C. to 900° C., and then performing a siliconizing treatment at 1400° C. to 1500° C. to prepare the carbon-ceramic composite material; The preparation step of the coating powder comprises: mixing a curing resin, silicon carbide, graphite and a metal oxide in a mass ratio of (20-50):60:(5-15):(1-2), kneading at 60°C-80°C, and crushing to prepare the coating powder; the metal oxide comprises one or more of aluminum oxide and yttrium oxide; The silicon / aluminum composite material comprises a substrate and a coating layer coated on the surface of the substrate, wherein the substrate comprises silicon; the coating layer comprises a thermosetting resin, graphite, aluminum and silicon carbide; The mass ratio of the substrate to the coating layer is (8-10): (0.3-1).
2. The method for preparing the carbon-ceramic composite material according to claim 1, characterized in that: The mass ratio of the thermosetting resin, the graphite, the aluminum element and the silicon carbide is (10-25): (5-10): (3-8): (1-2).
3. The method for preparing the carbon-ceramic composite material according to claim 1, characterized in that: The silicon / aluminum composite material has one or more of the following characteristics: (1) The thermosetting resin includes a phenolic resin; (2) The particle size of the graphite is 100 mesh to 1000 mesh; (3) The particle size of the matrix is 1 mm to 4 mm; (4) The particle size of the silicon carbide is 1 μm to 2 μm.
4. The method for preparing the carbon-ceramic composite material according to any one of claims 1 to 3, characterized in that: In the step of preparing the coating preform, the process parameters of the pressing molding include: a pressing temperature of 150° C. to 200° C. and a pressure of 2 MPa to 4 MPa.
5. The method for preparing the carbon-ceramic composite material according to any one of claims 1 to 3, characterized in that: The embryo body includes a resin-based embryo body or a carbon-carbon embryo body; the embryo body has one or more of the following characteristics: (1) The steps of preparing the resin-based embryo include: mixing carbon fiber, solid resin and graphite powder in a mass ratio of (30-60): (25-35): (10-30) to prepare a raw material; and pressing the raw material into a shape to prepare the resin-based embryo; (2) The steps of preparing the carbon-carbon embryo include: subjecting a carbon fiber preform to vacuum heat treatment and then subjecting it to chemical vapor deposition to prepare the carbon-carbon embryo.
6. The method for preparing the carbon-ceramic composite material according to claim 5, characterized in that: The preparation method has one or more of the following characteristics: (1) In the step of preparing the resin-based embryo, the process parameters of the pressing molding include: a pressing temperature of 150° C. to 200° C. and a pressure of 2 MPa to 4 MPa; (2) In the step of preparing the carbon-carbon embryo, the process parameters of the vacuum heat treatment include: pressure <1 kPa, temperature 900°C~1100°C; (3) In the step of preparing the carbon-carbon embryo, the process parameters of chemical vapor deposition include: the chemical reaction gas is natural gas and propane, the deposition pressure is 1.5 kPa~2.5 kPa, and the deposition temperature is 950℃~1000℃.
7. The method for preparing the carbon-ceramic composite material according to any one of claims 1 to 3, characterized in that: The preparation steps of the silicon / aluminum composite material include: The thermosetting resin, graphite powder, aluminum powder, silicon carbide and an organic solvent are mixed to prepare a slurry; The substrate is mixed with the slurry, and after drying, the silicon / aluminum composite material is prepared; Wherein, the mass ratio of the matrix and the slurry is (8-10):
1.
8. The method for preparing the carbon-ceramic composite material according to claim 7, characterized in that: The mass ratio of the thermosetting resin, the graphite powder, the aluminum powder, the silicon carbide and the organic solvent is (10-25): (5-10): (3-8): (1-2): (8-15).
9. The method for preparing the carbon-ceramic composite material according to claim 7, characterized in that: The drying process parameters include: a temperature of 75°C to 85°C.
10. A carbon-ceramic composite material, characterized in that: The carbon-ceramic composite material is prepared by the preparation method of any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method for silicon carbide fiber reinforced boron carbide ceramic material
CN108911773A
Carbon ceramic brake disc
CN117902910A
Cited By
Carbon-ceramic composite material and preparation method of carbon-ceramic composite material by utilizing cured resin waste
CN122301571A